GONADOTROPIN-RELEASING HORMONEAGONISTS AND ANTAGONISTS: INFLUENCE ON NEUROANGIOGENESIS AND APOPTOSIS IN EUTOPIC ENDOMETRIUM IN A THERAPY FOR RECURRINGENDOMETRIOSIS GENITALIS EXTERNA-ASSOCIATED PELVIC PAIN IN PATIENTS - Orazov, M. R.; Radzinsky, V. Y.; Khamoshina, M. B.; Lokshin, V. N.; Demyashkin, G. A.; Toktar, L. R.; Tokayeva, E. C.; Chitanava, Yu. S. (Scientific Journal of Pedagogy and Economics, 2018)
Endometriosis is one of the most common gynecological diseases diagnosed in almost 70% of patients with chronic pelvic pain (CPP). However, quarter of women with pelvic pain was diagnosed with external genital endometriosis (EGE) during laparoscopy. A special group is represented by patients with PPthat did not stop after the removal of endometrial foci. The mechanisms of the pathogenesis of the formation of pain syndrome are not completely explored yet. According to a number of authors, significant rolein the pathogenesis of pelvic pain recurrence after surgical treatment of EGE is played by active neuroangiogenesis, both in ectopic and eutopic endometrium.GnRh agonists are the “golden standard” for the treatment of endometriosis and highly effective against pelvic pain associated therewith. In a number of European countries, GnRh antagonists have been registered for the treatment of EGE-associated PP. Taking into account not fully discovered mechanisms of PP development in cases of EGE, the study of the expression of neurovascular markers in eutopic endometrium during aGnRh and antGnRh therapy was of scientific interest